Bullingers Familiengeschichte: Edition und Kommentar - Stettler, Bernhard (Zwingliana, 2015)
Annotated edition of the family history of Heinrich Bullinger with introduction,glossary and index. In 1568, Bullinger looks back and recalls his family’s history. His immediate relatives are introduced with many enlightening details, those of the inlaws only in list form. The events are committed to God’s grace. Bullinger, member of a family long-established in the town of Bremgarten in Aargau, finds his way to Zurich during the turbulences of the Reformation. His rise to become the successor of the reformer Huldrych Zwingli is experienced as God-decreed, and he and his descendants are able to integrate seamlessly into the leading elites of Zurich.